DEVELOPMENT OF AN AUTOMATED METHOD TO PERFORM A QUANTITATIVE STUDY OF PARTICLE SIZE DISTRIBUTION AND THE EFFECT OF A CONDUCTIVE LAYER IN SCANNING ELECTRON MICROSCOPY - Barreto, Juan C. G.; Tita, Diego L.; Orlandi, Marcelo O. (Sociedade Brasileira de Química, 2019)
The determination of particle size distribution is an important parameter for controlling industrial processes, particularly in the field of pharmaceuticals. It is also an important parameter for characterizing nanoparticles. The best technique for determining particle size distribution is scanning electron microscopy. The process of counting particles is typically performed manually, which requires both more time and a higher standard deviation than automatic methods. This study shows the results of a particle counting procedure that relies on a fully automated method that was found to improve the reproducibility of the measurement. The effect on the diameter of near-spherical polymer nanospheres between 20 and 100 nm (mean of 60 nm) when samples were coated by a conducting layer (such as gold or carbon) was also evaluated. The images were collected using a field emission scanning electron microscope and then processed using the ImageJ program. Results showed that the method proposed in this work produces mean diameter values in accordance with NIST-traceable near-spherical polymer nanospheres for the sample without coating. The study also revealed two main effects of the conductive coating: changes to topography and an increase in mean particle diameter.
Keywords: particle size distribution; near-spherical polymer nanoparticles; gold coating; carbon deposition; scanning electron microscopy